CLINICAL SIGNIFICANCE OF THE DENSITY OF TUMOR MICROVESSELS IN BREAST CANCER IN MEN - Lola T. Alimkhodjaeva; Munira H. Norbekova (Central Asian Journal of Medicine, 2022)
Breast cancer in men is a rare disease that accounts for less than 1% of all breast tumors. Currently, there is a need for research and search for new biomarkers for early diagnosis, monitoring of the course and prognosis of the disease, and in this aspect, the assessment of angiogenesis is of great importance. Taking into account the fact that the heterogeneity of tumor microvessels in breast cancer has not been practically studied, correlations of different types of vessels with clinical, morphological and molecular biological factors of disease prognosis, as well as with the severity of inflammatory infiltration of the tumor stroma and features of expression have not been studied, the purpose and objectives of this study have been determined.